2017
DOI: 10.3390/su9071195
|View full text |Cite
|
Sign up to set email alerts
|

The Supply Chain Design for Perishable Food with Stochastic Demand

Abstract: It has been a challenging task to manage perishable food supply chains because of the perishable product's short lifetime, the possible spoilage of the product due to its deterioration nature, and the retail demand uncertainty. All of these factors can lead to a significant amount of shortage of food items and a substantial retail loss. The recent development of tracing and tracking technologies, which facilitate effective monitoring of the inventory level and product quality continuously, can greatly improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 21 publications
0
23
0
2
Order By: Relevance
“…Numerous earlier studies have focused on showing the benefits of implementing dynamic pricing for perishables [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Past studies using a deterministic simulation showed that inventory aging of perishable foods can be reduced by applying various dynamic pricing strategies [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous earlier studies have focused on showing the benefits of implementing dynamic pricing for perishables [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Past studies using a deterministic simulation showed that inventory aging of perishable foods can be reduced by applying various dynamic pricing strategies [25].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have focused on finding the optimal supply chain design for perishable foods that optimizes inventory levels and pricing. For example, Yang et al [20], Xiao and Yang [21] developed models for the joint decisions of pricing, shelf space allocation, and replenishment strategies for perishables to maximize retailers' profitability. Yang et al [22] developed a supply chain model that considers pricing and temperature controls for perishable foods.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is beneficial to understand the effects of consumer demand on inventory management for suppliers and retailers [19]. Besides the economics benefits, this knowledge is crucial to the sustainability of the system as unsalable products cause significant environmental impacts [6].…”
Section: The Effects Of Consumer Demandmentioning
confidence: 99%
“…This research relates to a rich literature stream regarding the perishable supply chain where Yang et al [6] highlighted that it is a challenging task to manage a perishable supply chain due to uncertainty in product lifetime and customer demand. This research contributes to the literature on perishable supply chain by considering a two-echelon model with three perishable products.…”
Section: Introductionmentioning
confidence: 99%